The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.heliyon.2020.e05091
|View full text |Cite
|
Sign up to set email alerts
|

A framework for developing a spatial high-resolution daily precipitation dataset over a data-sparse region

Abstract: This paper outlines a framework in order to provide a reliable and up-to date local precipitation dataset over Sistan and Baluchestan province, one of the poorly rain gauged areas in Iran. Initially, the accuracy of GPCC data, as the reference dataset, was evaluated. Next, the performance of eight gridded precipitation products (namely, CHIRPS, CMORPH-RAW, ERA5, ERA-Interim, GPM-IMERG, GSMaP-MVK, PERSIANN and TRMM3B42) were compared based on the GPCC observations during 1982–2016 over the study area. The evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 63 publications
(88 reference statements)
1
5
0
Order By: Relevance
“…However, further improvements were still needed for their estimation and detection capabilities. Specifically, ERA5 generally overestimated precipitation and mis-detected many non-precipitation events, which is previously reported in the Tibetan Plateau 124 , southern China 125 , Austria 46 , North America 48 , and Iran 58 . This probably stems from the imperfections in the cumulus parameterizations over steep mountain slopes 126 .…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…However, further improvements were still needed for their estimation and detection capabilities. Specifically, ERA5 generally overestimated precipitation and mis-detected many non-precipitation events, which is previously reported in the Tibetan Plateau 124 , southern China 125 , Austria 46 , North America 48 , and Iran 58 . This probably stems from the imperfections in the cumulus parameterizations over steep mountain slopes 126 .…”
Section: Discussionsupporting
confidence: 50%
“…Tang et al concluded that IMERG generally outperformed ERA5 across China, and can better reproduce precipitation diurnal cycles 55 . Other studies were presented in Central Asia 56 , India 57 , Turkey 47 , Iran 58 , and the United States 59 . Most studies have shown that IMERG outperforms ERA5, but the superiority of each dataset varies by regions, precipitation intensity, and altitude.…”
Section: Introductionmentioning
confidence: 99%
“…PERSIANN-CDR performed better than CHIRPS for semiarid regions of Brazil [ 26 ]. GPM, GSMaP, and PERSIANN were all found to offer reliable near-real-time meteorological estimation of data-sparse regions in Iran [ 27 ]. Climate Prediction Center Morphing Method (CMORPH) outperformed TRMM and Integrated Multisatellite Retrievals for Global Precipitation Measurement (IMERG) for daily estimation of the precipitation in the Yellow River basin of China, while GSMaP and CHIRPS performed the worst.…”
Section: Introductionmentioning
confidence: 99%
“…The overestimation could also be related to the fact that ERA5 overestimates precipitation over high mountain ranges such as the Andes and Himalayas (Hassler & Lauer, 2021). Other studies have reported that ERA5 tends to overestimate precipitation and incorrectly identify numerous non‐precipitation events in various regions, including Austria (Sharifi et al, 2019), southern China (Gao et al, 2020), North America (Tarek et al, 2020), Iran (Yazdandoost et al, 2020), the Tibetan Plateau (Zhang et al, 2022) and the Mongolian Plateau (Xin et al, 2022). This is likely due to the limitations in the representation of cumulus parameterizations in high‐gradient mountain slopes (Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%